Influence of H&E and Papanicolau stains on DNA integrity: systematic review - Pote, Alexandra (2019)
The success of the Human Genome Project along with the development of new molecular and bioinformatics methods has allowed a rapid evolution of personalized health care. In that context, molecular pathology plays a key role in providing patient-specific disease signatures allowing to develop targeted and patient-driven therapeutic strategies and to predict therapeutic response, particularly in oncology. For that, the presence or absence of mutations is assessed by molecular techniques such as polymerase chain reaction (PCR), Sanger sequencing and next-generation sequencing (NGS). This information complements the morphological analysis obtained by microscopic inspection of tissue sections, commonly from formalin-fixed paraffin-embedded (FFPE) samples, or of cytological specimens (CS). As cells and other tissue components are invisible, to render them visible under the microscope, it is necessary to perform a previous staining procedure. The routine stain in clinical pathology laboratories for FFPE samples is Hematoxylin and Eosin (H&E), as it allows the visualization of general tissue architecture assisting the evaluation of structural and morphological changes. For cytological specimens, the routine stain is Papanicolau (Pap). In some cases, FFPE or CS samples are scarce and it is necessary to extract DNA directly from FFPE or CS stained-samples. Furthermore, samples from tumors are usually very heterogeneous containing a variable mixture of neoplastic cells and a variety of normal cells. Molecular analysis of DNA extracted from these mixtures can lead to confusing or false negative results and erroneous conclusions. In order to diminish the interference of normal cells, the tumor area is usually selected and isolated before molecular analysis is performed. This enrichment of neoplastic cells can be performed through manual or automated-assisted microdissection of FFPE, CS or frozen samples. In these cases, it is mandatory to extract nucleic acids directly from stained samples. Although this is a common practice in molecular pathology laboratories, a survey of the literature demonstrates that the reagents used in H&E and Pap stains may induce chemical modifications on DNA. This review collects the available information about the influence of H&E and Pap stains in DNA integrity and explores the mechanisms by which the dyes might interfere with molecular analysis, particularly on PCR-based methods.